1992
DOI: 10.1016/0378-1097(92)90369-y
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of macrolide 2′-phosphotransferase type II from a strain of Escherichia coli highly resistant to macrolide antibiotics

Abstract: The resistance mechanism of Escherichia coli BM2506 to macrolides was found to be due to inactivation. Inactivated oleandomycin was identified as oleandomycin 2'-phosphate by thin-layer chromatography. A new type of macrolide-phosphorylating enzyme, macrolide 2'-phosphotransferase type II (MPH(2')II), was detected, purified 95-fold and its enzymological properties investigated. MPH(2')II was a constitutive intracellular enzyme which showed high levels of activity with both 14-member-ring and 16-member-ring mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
51
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 26 publications
1
51
1
Order By: Relevance
“…Therefore, even though they are thermodynamically equivalent, ATP versus GTP utilization is biochemically segregated. It was therefore surprising that our research, as well as several literature reports using purified APH and MPH enzymes, revealed that many of these enzymes can use both ATP and GTP (2,13,16). Indeed, this preference was recently used as the basis for a proposed new nomenclature for APH(2Љ) enzymes (21).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Therefore, even though they are thermodynamically equivalent, ATP versus GTP utilization is biochemically segregated. It was therefore surprising that our research, as well as several literature reports using purified APH and MPH enzymes, revealed that many of these enzymes can use both ATP and GTP (2,13,16). Indeed, this preference was recently used as the basis for a proposed new nomenclature for APH(2Љ) enzymes (21).…”
Section: Discussionmentioning
confidence: 79%
“…These antibiotic kinases have largely been seen to use the phosphoryl donor ATP as the second substrate for antibiotic modification, consistent with the primacy of this nucleotide triphosphate (NTP) in primary metabolism and the intracellular concentration of ϳ3 mM in bacterial cells (1). During our efforts to characterize the structure and mechanism of macrolide antibiotic kinases, we were struck by the poor activity with ATP compared to GTP as a phosphoryl donor substrate in in vitro assays, exhibiting a selectivity that had been noted previously but was unexplored (13). This preference was surprising to us, given the reported intracellular concentrations of ATP versus GTP, which in bacterial and mammalian cells are reported to be on the order of 3-to 4-fold in excess of ATP (3; reviewed in reference 20).…”
mentioning
confidence: 99%
“…The corresponding genes, which encode type I (mphA) and type II (mphB) macrolide 2Ј-phosphotransferases, confer a high level of resistance to several macrolides in E. coli. This resistance mechanism is a consequence of a modification of the active macrolide by phosphorylation within the sugar moiety (28,41). From the observed similarities, we can postulate that the ORF2 product might well be involved in phosphorylation of some intermediate substrate of the streptothricin biosynthetic pathway.…”
Section: Resultsmentioning
confidence: 93%
“…However, macrolideinactivating enzymes, namely, EM esterases (1,20) and macrolide 2Ј-phosphotransferases (10,19), that mediate such resistance have been found in clinical isolates of Escherichia coli, which is naturally resistant to macrolides. Furthermore, almost all macrolide-inactivating enzymes are constitutively produced in E. coli (1,2,10,20). However, the production of macrolide 2Ј-phosphotransferase I [Mph(A); formerly MPH(2Ј)I] (22), which is a strong inactivator of 14-member ring macrolides, such as EM and oleandomycin (OL), is induced by EM in the original strain E. coli Tf481A (19).…”
mentioning
confidence: 99%